1999
DOI: 10.1046/j.1365-2958.1999.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase Mkp1 of Pneumocystis carinii complements the slt2Δ defect in the cell integrity pathway of Saccharomyces cerevisiae

Abstract: Signal transduction pathways are important in the adaptive response of microbes to their environment. A Pneumocystis carinii extracellular signal‐regulated protein kinase (MAPK) homologue, Mkp1, has been isolated by sequence similarity screening of P. carinii genomic DNA. The Mkp1 of P. carinii shows closest homology to other fungal MAP kinases involved in cell integrity signal transduction cascades, including Slt2p/Mpk1p of Saccharomyces cerevisiae, Mkc1 of Candida albicans and Mps1 of Magnaporthe grisea. Def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Although evidences exist that hydrogen peroxide activates p44/p42 MAPK in mammalian cells, our results show for the first time activation of p44/p42 MAPK by hydrogen peroxide in the yeast S. cerevisiae (Hannken et al, 2000;Nguyen et al, 2004;van Rossum et al, 2004). Interestingly Mkp1, a Pneumocystis carinii homologue of Mpk1, has been found to be activated by the same oxidant (Fox and Smulian, 1999).…”
Section: Discussionmentioning
confidence: 44%
“…Although evidences exist that hydrogen peroxide activates p44/p42 MAPK in mammalian cells, our results show for the first time activation of p44/p42 MAPK by hydrogen peroxide in the yeast S. cerevisiae (Hannken et al, 2000;Nguyen et al, 2004;van Rossum et al, 2004). Interestingly Mkp1, a Pneumocystis carinii homologue of Mpk1, has been found to be activated by the same oxidant (Fox and Smulian, 1999).…”
Section: Discussionmentioning
confidence: 44%
“…PHR class genes have been implicated in cell wall generation, cross-linking, and stability under adverse conditions. Heterologous expression of P. carinii genes in culturable fungal species has recently proven a useful experimental approach to infer P. carinii gene function (10,17,36). Accordingly, we evaluated the ability of P. carinii PHR1 to growth complement an S. cerevisiae mutant strain deficient in the PHR1 analogue GAS1 in the presence of a potent osmotic destabilizing agent, SDS (38).…”
Section: Resultsmentioning
confidence: 99%
“…We could not detect significant changes in H 2 O 2 induction of SLT2 in hog1⌬ and PTP2 induction in slt2⌬ or hog1⌬ strains (data not shown). It has been shown that Mkp1, an Slt2 homologue of Pneumocystis carinii, can be activated by H 2 O 2 in vitro (39). However, it remains to be ascertained whether Slt2 can be activated by H 2 O 2 and whether this activation is responsible for H 2 O 2 induction of PTP2 and SLT2.…”
Section: Differential Expression Of Slt2 and Phosphatase Genes In Resmentioning
confidence: 99%